METTL14 regulates proliferation and differentiation of duck myoblasts through targeting MiR-133b - Qicheng Jiang; Tieshan Xu; Hailong Zhou; Zhepeng Xiao; Lingjing Xing; Xinli Zheng; Ping Yu; Zhe Chao; Zhongchun He; Wei Yang; Lihong Gu (PLoS ONE, 2025)
The development of duck pectoral muscle has a significant impact on meat quality, and miRNA and m6A modification play key roles in this process. In the early stage, by using MeRIP-seq and miRNA-seq to analyze the pectoral muscle tissue of duck embryos at day 13 (E13), day 19 (E19), and day 27 (E27) of incubation, we found that METTL14, as a core component of the m6A methylation transferase complex, showed significant differences in expression at different developmental stages and may have an important impact on pectoral muscle development. In this study, qRT-PCR detection revealed that the expression of proliferation and differentiation marker genes CDK2, CyclinD1, MYOG and MYHC varied at different stages, with the highest m6A level at E13 and the lowest expression of METTL14 at the same stage. After constructing overexpression and interference vectors for METTL14, we found that METTL14 interference promoted the proliferation of duck embryo myoblasts and inhibited differentiation, while overexpression inhibited proliferation and accelerated differentiation. In particular, the overexpression of METTL14 increased the expression of miR-133b, whose precursor sequence contains m6A modification sites, suggesting that METTL14 may participate in the regulation of muscle development by affecting the expression of miR-133b. This study provides new insights into the molecular mechanisms of duck pectoral muscle development and offers potential molecular targets for the genetic improvement of duck pectoral muscle.